Modelling the impact of lock-downs in top-4 COVID-19 spreading states of India. (4th October 2022) - Anand, Adarsh; Agarwal, Mohini; Aggrawal, Niyati; Bhatt, Navneet
A pandemic like COVID-19 being a highly infectious disease has severely affected mankind and business activities. Seeing the critical situation, the honourable Prime Minister of India has called for a lockdown in the entire country in order to suppress the spread of this pandemic. While there are many debates about the spread of disease and lockdown in the entire country, we wish to mathematically understand the diffusion of this pandemic in the context of four highly infected states of India. Moreover, through this paper, we wish to examine the impact of these lockdown periods in order to understand the spread of COVID-19.